Forging Brand Commitment through Service Quality and Customer Experience: The Moderating Role of Customer Trust - Ambo Masse; Ami Nurhayati; Astil Harli Roslan; Nofal Supriaddin; Syahra (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of service quality and customer experience on brand commitment, with brand image as a mediating variable and customer trust as a moderating variable among car customers in Kendari City. Methods: This study employed an explanatory quantitative approach. Methods: This study employed an explanatory quantitative approach. A total of 200 car customers in Kendari City were selected using purposive sampling. Data were collected through a structured questionnaire and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). Results: The findings indicate that service quality and customer experience have significant effects on brand image and brand commitment. Brand image was found to mediate the relationship between service quality, customer experience, and brand commitment. In addition, customer trust significantly strengthens the effect of brand image on brand commitment. These results show that better service quality and more positive customer experience contribute to stronger brand image and higher customer commitment to the brand. Implications: The results suggest that automotive companies need to improve service quality, create positive customer experiences, strengthen brand image, and build customer trust to sustain long-term customer relationships. This study is limited to car customers in Kendari City and uses a cross-sectional design. Therefore, future studies are recommended to expand the research area, apply a longitudinal design, and include other relevant variables to provide a more comprehensive understanding of brand commitment